Oxidative Stress and Assisted Reproduction: A Comprehensive Review of Its Pathophysiological Role and Strategies for Optimizing Embryo Culture Environment - Ashok Agarwal; Israel Maldonado Rosas; Christina Anagnostopoulou; Rossella Cannarella; Florence Boitrelle; Lina Villar Munoz; Renata Finelli; Damayanthi Durairajanayagam; Ralf Henkel; Ramadan Saleh (Antioxidants, 2022)
Oxidative stress (OS) due to an imbalance between reactive oxygen species (ROS) and antioxidants has been established as an important factor that can negatively affect the outcomes of assisted reproductive techniques (ARTs). Excess ROS exert their pathological effects through damage to cellular lipids, organelles, and DNA, alteration of enzymatic function, and apoptosis. ROS can be produced intracellularly, from immature sperm, oocytes, and embryos. Additionally, several external factors may induce high ROS production in the ART setup, including atmospheric oxygen, CO2 incubators, consumables, visible light, temperature, humidity, volatile organic compounds, and culture media additives. Pathological amounts of ROS can also be generated during the cryopreservation-thawing process of gametes or embryos. Generally, these factors can act at any stage during ART, from gamete preparation to embryo development, till the blastocyst stage. In this review, we discuss the in vitro conditions and environmental factors responsible for the induction of OS in an ART setting. In addition, we describe the effects of OS on gametes and embryos. Furthermore, we highlight strategies to ameliorate the impact of OS during the whole human embryo culture period, from gametes to blastocyst stage.